1960
DOI: 10.1111/j.2153-3490.1960.tb01283.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Coastal Generation of Internal Tides

Abstract: Differential equations, boundary, and discontinuity conditions are obtained which relate the internal tide to the surface tide in a two‐layer system. Solutions of these equations give internal tides which may be large compared to the surface tide. In the coastal region these internal tides are standing waves and further offshore they attain the characteristics of progressive waves traveling seaward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
2

Year Published

1980
1980
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 4 publications
2
34
1
2
Order By: Relevance
“…Zeilon [1912,1934] was the first who studied theoretically and by experiments the influence of bottom topography on tides in a two-layer system and showed that internal tides develop. The results were confirmed by Rattray [1960] for the shelf break and were later extended to continuous stratification [Rattray et al, 1969]. According to the theory, beams of baroclinic energy should emanate from the shelf edge into the deep ocean (along characteristics).…”
Section: Introductionsupporting
confidence: 60%
“…Zeilon [1912,1934] was the first who studied theoretically and by experiments the influence of bottom topography on tides in a two-layer system and showed that internal tides develop. The results were confirmed by Rattray [1960] for the shelf break and were later extended to continuous stratification [Rattray et al, 1969]. According to the theory, beams of baroclinic energy should emanate from the shelf edge into the deep ocean (along characteristics).…”
Section: Introductionsupporting
confidence: 60%
“…The first simple analytical model describing the generation of internal tides was presented by Rattray (1960). He described the analysis of two-layer system with an abrupt change of topography under presumption of long waves, and showed that this model gives an amplification of internal tides with respect to surface tides.…”
Section: Analytical Modelling Of Internal Tidesmentioning
confidence: 99%
“…Introduction of real topography and continuous density distribution limits the possibilities of analytical modeling, making numerical approach the only possible altermative. Analytical solutions of idealized model were also considered for linear shelf slope between the coast and depth discontinuity (Rattray, 1960), and for linear discontinuity slope (Prinsenberg and Rattray, 1975). Modal approach described by Prinsenberg and Ratlray (1975) is appropriate for linear shelf slope and any given stratification, whilst Baines (1982) presented analytical models that are applying different approach in internal tide research, based on the ray theory.…”
Section: Analytical Modelling Of Internal Tidesmentioning
confidence: 99%
“…A interação entre as correntes de maré barotrópicas e irregularidades na batimetria do fundo oceânico cria perturbações verticais na estrutura de densidade da coluna d'água. Tais perturbações podem se propagar tanto em direçãoà costa quanto ao oceano profundo como OGI com períodos distintos, mas por vezes com frequências iguaisàs da sua forçante original (ZEILON, 1912;ZEILON, 1914;RATTRAY, 1960;WUNSCH, 1975), sendo, então, chamadas marés internas ou marés baroclínicas.…”
Section: Introductionunclassified
“…Na plataforma continental, Rattray (1960) A carga de sedimentos associadaà descarga do RAé de aproximadamente 1, 3 × 10 9 ton.ano -1 (MEADE et al, 1985;MEADE, 1994). Esses sedimentos formam grandes concentrações próximo ao fundo, denominadas lama fluida (GEYER et al, 1996), diminuindo o atrito com o fundo e, assim, influenciando as características hidrodinâmicas locais.…”
Section: Introductionunclassified